Frequency of Tuberculosis in Cervical Lymphadenopathy at Tertiary Care Hospital - Iftikhar Ali Kakar, Nasir Azim, Abdul Baqi, Yasir Arfat, Ayesha Abbas, Khalid Shahab, Muhammmad Idrees, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Tuberculosis is a major public health concern, and it is the most prevalent cause of infectious disease that infects the lymphoid tissue of the body. Clinicians have a diagnostic challenge when treating chronic enlargement of cervical lymph node since it may be a sign of a more serious condition. Objective: To assess the frequency of tuberculosis in cervical lymphadenopathy at tertiary care hospital Methodology: This descriptive study was undertaken at the Department of Pulmonology, Fatima Jinnah Institute of Chest Diseases and Sheikh Khalifa Bin Zayyed Al Nahyan Medical Complex Quetta from October 2021 to October 2022. A complete physical examination was performed after taking a detailed medical history from each patient. A pre-designed proforma was used for the collection of all required data. SPSS version 23 was used to analyze all of the data. Results: In the current study, 140 patients were enrolled. There were 84 (60%) male participants while female participants were 56 (40%). The overall frequency of tuberculosis in patients with cervical lymphadenopathy was 98 (70%). Conclusion: Our study concludes that tuberculosis is the prevalent cause of cervical lymphadenopathy. All the patients with cervical lymphadenopathy must be diagnosed for tuberculosis. Keywords: Frequency; tuberculosi; csservical lymphadenopathy